1989
DOI: 10.1063/1.343913
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of electron energy deposition necessary to form an anode plasma in Ta, Ti, and C for coaxial bremsstrahlung diodes

Abstract: A possibility of plasma current density measurements using suprathermal electron Bremsstrahlung emission Rev.Measurements are made of surface doses necessary to initiate an anode plasma by electron bombardment of Ta, Ti, and C anodes for coaxial geometries characteristic of high-power electron-beam diodes. Measured lower and upper bcunds of doses necessary to form an anode plasma are 54 ± 7-139 ± 16 Jig in Ta, 214 ± 23-294 ± 71 Jig in Ti, and 316 ± 33-494 ± 52Jig in C. Within these bounds, probable values for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…The model assumes SCL emission of ions (H þ ) directly from surfaces for which the local temperature has increased by 400 K. This threshold condition for anode ion emission is based on experimental evidence from high-power, charged-particle diode experiments (see, for example, Refs. [26,27]). …”
Section: Simulation Modelmentioning
confidence: 99%
“…The model assumes SCL emission of ions (H þ ) directly from surfaces for which the local temperature has increased by 400 K. This threshold condition for anode ion emission is based on experimental evidence from high-power, charged-particle diode experiments (see, for example, Refs. [26,27]). …”
Section: Simulation Modelmentioning
confidence: 99%
“…Often, this results in areas of high current density on the anode which heats the anode surface. When the anode surface temperature is raised about 400 °C it is observed that a plasma forms on the anode surface which becomes a strong emitter of ions [3], a process called thermal ion emission.…”
Section: Emission Processes In High-power Cross-field Vacuum Devicesmentioning
confidence: 99%
“…Blaugrund [47] observed this with electron beam pinches when the anode temperature reaches 400 °C. Sanford [48] observed that anode plasma forms on metals at about 400 °C. For most shots it was possible to get a good fit at 400 °C if the incident beam radius was expanded by ~1 mm.…”
Section: Large Gapsmentioning
confidence: 99%